Numerical investigation of methane and formation fluid leakage along the casing of a decommissioned shale gas well. Issue 6 (25th June 2015) - Nowamooz, A.; Lemieux, J.‐M.; Molson, J.; Therrien, R.
Abstract Methane and brine leakage rates and associated time scales along the cemented casing of a hypothetical decommissioned shale gas well have been assessed with a multiphase flow and multicomponent numerical model. The conceptual model used for the simulations assumes that the target shale formation is 200 m thick, overlain by a 750 m thick caprock, which is in turn overlain by a 50 m thick surficial sand aquifer, the 1000 m geological sequence being intersected by a fully penetrating borehole. This succession of geological units is representative of the region targeted for shale gas exploration in the St. Lawrence Lowlands (Québec, Canada). The simulations aimed at assessing the impact of well casing cementation quality on methane and brine leakage at the base of a surficial aquifer. The leakage of fluids can subsequently lead to the contamination of groundwater resources and/or, in the case of methane migration to ground surface, to an increase in greenhouse gas emissions. The minimum reported surface casing vent flow (measured at ground level) for shale gas wells in Quebec (0.01 m3/d) is used as a reference to evaluate the impact of well casing cementation quality on methane and brine migration. The simulations suggest that an adequately cemented borehole (with a casing annulus permeability kc<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj22dvqfr7" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />≤</alternatives> 1 mD) can prevent methane and brine leakage over a time scale of up to 100 years. However, a poorly cemented borehole (kc<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj22dvqfx0" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />≥</alternatives> 10 mD) could yield methane leakage rates at the base of an aquifer ranging from 0.04 m3/d to more than 100 m3/d, depending on the permeability of the target shale gas formation after abandonment and on the quantity of mobile gas in the formation. These values are compatible with surface casing vent flows reported for shale gas wells in the St. Lawrence Lowlands (Quebec, Canada). The simulated travel time of methane from the target shale formation to the surficial aquifer is between a few months and 30 years, depending on cementation quality and hydrodynamic properties of the casing annulus. Simulated long‐term brine leakage rates after 100 years for poorly cemented boreholes are on the order of 10−5 m3/d (10 mL/d) to 10−3 m3/d (1 L/d). Based on scoping calculations with a well‐mixed aquifer model, these rates are unlikely to have a major impact on groundwater quality in a confined aquifer since they would only increase the chloride concentration in a pristine aquifer to 1 mg/L, which is significantly below the commonly recommended aesthetic objective of 250 mg/L for chloride.